Copper conductive ink material preparation device and method
By designing a copper conductive ink material preparation device, using an airtight glove box, solid-liquid separator and ventilation filtration system, the problems of flammable and explosive raw materials and dust-free environment in the production of copper conductive ink material are solved, and high-quality copper conductive ink material preparation is achieved.
Patent Information
- Application Number
- CN202411944771.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-25
AI Technical Summary
In the production process of copper conductive ink materials, flammable and explosive powders and formic acid raw materials need to be used, and the production environment needs to be kept dust-free, making it difficult to achieve high-quality production in the prior art.
A copper conductive ink material preparation device is designed, including an airtight glove box stacked up and down and a solid-liquid separator. The local temperature and air pressure are controlled by heating agitator and suction device, and combined with a ventilation filtration system and a solid-liquid separator, the high-quality preparation of copper conductive ink material is achieved.
It effectively ensures the safety of the test personnel, avoids the release of harmful gases, maintains the cleanliness of the production environment, reduces the entry of dust particles, and realizes the preparation of high-quality copper conductive ink materials.
Smart Images

Figure CN119869293A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of conductive ink material preparation, and more specifically, to a copper conductive ink material preparation device and method. Background Art
[0002] Copper conductive ink can be printed on curved surface components by inkjet printing to form conformal circuits. Conformal circuits have a wide range of applications and significant advantages. For example, conformal antennas on the surface of drones can greatly reduce their own weight, reduce radar reflection area, and improve maneuverability, aerodynamics, and stealth.
[0003] The technical solutions for preparing copper conductive ink materials in the prior art include:
[0004] (1) A Chinese invention patent with publication number CN116285503B discloses a particle-free copper conductive ink and a conductive copper film for 3D inkjet printing and a preparation method thereof. The particle-free copper conductive ink comprises the following components by mass fraction: copper formate tetrahydrate: 25wt%-45wt%; complexing agent: 35wt%-45wt%; auxiliary agent: 4wt%-6wt%; solvent: balance. The complexing agent is 1,2-propylenediamine and / or n-octylamine; the auxiliary agent is sodium dodecylbenzenesulfonate and / or hexadecyltrimethylammonium bromide, and the solvent is ethanol and / or methanol. The copper-based conductive ink of the present invention does not contain particulate matter, and the complexing agent and auxiliary agent components are added to the copper formate tetrahydrate system, and have high long-term storage stability. The auxiliary agent helps to reduce size differences and promote uniform particle distribution during the subsequent sintering process of preparing 3D printed products, and can also adjust the hydrophilic angle between the ink and the 3D printing substrate.
[0005] (2) A Chinese invention patent with publication number CN112111197A discloses a method for preparing a composite conductive ink comprising copper particles and an organic copper salt, comprising the following steps: (1) placing copper powder in a reaction kettle, heating and oxidizing at 100 to 300°C with stirring, reacting for 15 minutes to 2 hours, and then cooling to room temperature; (2) mixing formic acid, an organic amine, a solvent, and a stabilizer in proportion, heating to 45 to 85°C, adding the oxidized copper powder under stirring, and continuing the reaction for 20 to 60 minutes. After the reaction is completed, water and excess organic acid are removed by reduced pressure distillation to obtain a copper particle / organic copper salt composite conductive ink.
[0006] In the production process of copper conductive ink materials, flammable and explosive powders and formic acid raw materials are needed, and the production environment needs to be kept dust-free. Therefore, a copper conductive ink material preparation device and method are needed to achieve high-quality production. Summary of the invention
[0007] To solve the above problems, the technical solution adopted in the present application is a copper conductive ink material preparation device, comprising an upper airtight glove box and a lower airtight glove box stacked up and down, a solid-liquid separator is arranged between the upper airtight glove box and the lower airtight glove box; a heating agitator is arranged in the upper airtight glove box, and an air suction device is arranged around the heating agitator; a sodium carbonate powder injector, a formic acid liquid injector, a copper sulfate solution sealed bottle and a copper formate crystal sealed bottle are arranged in the upper airtight glove box, the upper airtight glove box is provided with a ventilation filtration system, the ventilation filtration system is provided with an argon gas supply port, and the ventilation filtration system can provide a drying box in the lower airtight glove box, the upper airtight glove box and the lower airtight glove box are both provided with operating holes, operating gloves and airtight doors, and an air pressure detection device, a distilled water inlet pipe and an ethanol inlet pipe are arranged in the upper airtight glove box.
[0008] Optionally, a wind curtain device for supplying air from top to bottom is provided on the top of the airtight door.
[0009] Optionally, the number of heating stirrers is m×n, wherein m is the number of rows, n is the number of columns, m≥2, n≥2.
[0010] Optionally, the ventilation and filtering system is arranged between the upper airtight glove box and the lower airtight glove box, and shares an air flow passage with the air suction device.
[0011] Optionally, the solid-liquid separator includes an inner cylinder, a funnel arranged in the upper airtight glove box and an outer cylinder arranged in the lower airtight glove box, the bottom of the outer cylinder is locked by a stopper through a Morse taper seal, and a filter membrane is fixed to the bottom of the inner cylinder through a sealing ring, and the pore size of the filter membrane is 30-50 microns.
[0012] The present application also provides a method for preparing a copper conductive ink material, which is manufactured using any of the aforementioned copper conductive ink material preparation devices.
[0013] Optionally, the following steps are included:
[0014] S1: Place a quartz sealed bottle containing copper sulfate solution, a quartz sealed bottle containing formic acid, an empty quartz sealed bottle, and vacuum-packed sodium carbonate powder into an upper airtight glove box, place the empty quartz sealed bottle into a lower airtight glove box, complete the sealing of the upper and lower airtight glove boxes, and start the ventilation and filtration system;
[0015] S2: heating and stirring the copper sulfate solution, and adding the material to the sodium carbonate powder injector and the formic acid liquid injector;
[0016] S3: adding sodium carbonate to the copper sulfate solution through a sodium carbonate powder injector under heating and stirring conditions until the sodium carbonate is completely dissolved, and controlling the air pressure in the upper airtight glove box to 98-104 kPa through an air suction device to obtain a sodium carbonate-copper sulfate mixed solution;
[0017] S4: separating the sodium carbonate-copper sulfate mixed solution by a solid-liquid separator to obtain copper carbonate hydroxide crystals, purifying and recovering the copper carbonate hydroxide crystals;
[0018] S5: adding formic acid to the copper carbonate hydroxide crystals through a formic acid injector, heating and stirring, and controlling the air pressure in the upper airtight glove box to 98-104 kPa through an aspirator to obtain a copper carbonate hydroxide-formic acid mixed solution;
[0019] S6: distilling the sodium carbonate hydroxide-formic acid mixed solution obtained in step S5 to obtain a copper formate solution;
[0020] S7: separating the copper formate solution by a solid-liquid separator to obtain copper formate crystals, purifying and recovering the copper formate crystals;
[0021] S8: The air inside the upper airtight glove box is replaced with argon gas through a ventilation and filtration system, and copper formate crystals are taken and heated to 200° C. to prepare a copper nanoparticle size detection sample.
[0022] Optionally,
[0023] Step S4, separating the copper carbonate-sodium sulfate mixed solution by a solid-liquid separator to obtain copper carbonate hydroxide crystals, comprises: placing the sodium carbonate-copper sulfate mixed solution into a funnel of the solid-liquid separator, placing the inner cylinder into the funnel from top to bottom, allowing the sodium sulfate solution to pass through the sieve holes of the filter membrane into the inner cylinder, and the copper carbonate hydroxide crystals are intercepted by the filter membrane in the area between the inner cylinder and the funnel;
[0024] Step S7, separating the copper formate solution by a solid-liquid separator to obtain copper formate crystals, comprises: placing the copper formate solution into a funnel of the solid-liquid separator; placing the inner cylinder into the funnel from top to bottom, the copper formate solution enters the inner cylinder through the sieve holes of the filter membrane to form a solution containing impurities, and the copper formate crystals are intercepted by the filter membrane in the area between the inner cylinder and the funnel.
[0025] Optionally,
[0026] Step S4 purifying and recovering the copper carbonate hydroxide crystals includes: adding distilled water between the funnel and the inner cylinder, extracting the liquid inside the inner cylinder until the copper carbonate hydroxide crystals are purified, collecting the precipitated copper carbonate hydroxide crystals, and cleaning the inner cylinder and the sealing cone surface;
[0027] Step S7 of purifying and recovering the copper formate crystals includes: filling ethanol solution between the funnel and the inner cylinder, extracting the liquid inside the inner cylinder until the copper formate crystals are purified, collecting the precipitated copper formate crystals, and cleaning the inner cylinder and the sealing cone surface.
[0028] Optionally, during the distillation process of step S6, the copper carbonate hydroxide-formic acid mixed solution is kept from boiling, and it is required that copper formate cannot be completely crystallized at the end of the distillation.
[0029] The beneficial effects of the copper conductive ink material preparation device and method provided in this application are:
[0030] 1. Prepare the copper conductive ink material in the upper and lower airtight glove boxes of the copper conductive ink material preparation device, effectively ensure the safety of the test personnel, avoid inhaling volatile harmful gases generated by heating the formic acid-copper sulfate solution, and keep the environment of the copper conductive ink material preparation process relatively clean to reduce dust particles entering the copper conductive ink material;
[0031] 2. The local temperature is controlled to be stable by the air suction device arranged around the heating stirrer, the heat dissipation during the heating and stirring process is reduced, and the heat generated by the heating and stirring is prevented from affecting the raw materials pre-placed in the upper airtight glove box. At the same time, ventilation and filtration are performed to keep the internal pressure of the upper airtight glove box relatively stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments or descriptions of the prior art.
[0033] Figure 1 A schematic diagram of a copper conductive ink material preparation device provided in an embodiment of the present application;
[0034] Figure 2 A schematic diagram of a solid-liquid separation device for copper conductive ink material provided in an embodiment of the present application;
[0035] Figure 3 for Figure 2 A magnified view of the local area A;
[0036] Figure 4 for Figure 2 Enlarged view of local B.
[0037] Explanation of the reference numerals: 1-upper airtight glove box; 101-upper operating hole; 102-upper rubber gloves; 103-upper airtight door; 2-heating stirrer; 3-quartz sealing bottle; 4-sodium carbonate powder injector; 5-formic acid liquid injector; 6-upper tool box; 7-sodium carbonate powder bag; 8-solid-liquid separator; 801-funnel; 802-outer cylinder; 803-stopper; 804-sealing cone; 805-inner cylinder; 806-filter membrane; 807-sealing ring; 808-liquid level; 9. Lower airtight glove box; 901-lower operating hole; 902-lower rubber gloves; 903-lower airtight door; 10-lower tool box; 11-drying box; 12-suction device. DETAILED DESCRIPTION
[0038] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0039] like Figure 1 As shown, a copper conductive ink material preparation device comprises an upper airtight glove box 1 and a lower airtight glove box 9 stacked up and down, a solid-liquid separator 8 is arranged between the upper airtight glove box 1 and the lower airtight glove box 9; a heating stirrer 2 is arranged in the upper airtight glove box 1, and an air suction device 12 is arranged around the heating stirrer 2; a sodium carbonate powder injector 4, a formic acid liquid injector 5, a copper sulfate solution sealed bottle and a copper formate crystal sealed bottle are arranged in the upper airtight glove box 1. In this embodiment, the copper sulfate solution sealed bottle The sealed bottle for the copper formate crystal is a quartz sealed bottle 3, the upper airtight glove box 1 is provided with a ventilation and filtration system, the ventilation and filtration system is provided with an argon gas supply port, the lower airtight glove box 9 is provided with a drying box 11, the upper airtight glove box 1 is provided with an upper operation hole 101, an upper rubber glove 102 and an upper airtight door 103, the lower airtight glove box 9 is provided with a lower operation hole 901, a lower rubber glove 902 and a lower airtight door 903, and the upper airtight glove box 1 is provided with an air pressure detection device, a distilled water access pipe and an ethanol access pipe. The upper airtight glove box 1 and the lower airtight glove box 9 are also provided with an upper tool box 6 and a lower tool box 10, respectively, for storing experimental equipment required for preparing copper conductive ink.
[0040] The copper sulfate solution is prepared by dissolving copper sulfate anhydrate crystals (blue powdery crystals) in water (distilled water).
[0041] like Figure 1 As shown, in another embodiment of the present application, an air curtain device for supplying air from top to bottom is provided on the top of the upper airtight door 103 and the lower airtight door 903. When the airtight door is opened, the air curtain device reduces the number of dust particles entering the upper airtight glove box 1 and the lower airtight glove box 9.
[0042] like Figure 1 As shown, in another embodiment of the present application, the heating stirrers 2 are provided with m×n pieces, wherein m is the number of rows, n is the number of columns, m≥2, n≥2. Based on the high-throughput design concept, m×n heating stirrers 2 are provided, and m×n groups of experiments are performed simultaneously, which can fully maintain the consistency of experimental conditions and experimental environment, and based on the sodium carbonate powder injector 4 with three degrees of freedom movement and powder injection quality servo control function, and the formic acid injector 5 with three degrees of freedom movement and drip volume servo control function, sodium carbonate and formic acid are added according to the amount gradient designed by high-throughput, and m×n kinds of copper conductive ink materials are obtained under the same experimental environment conditions.
[0043] like Figure 1 As shown, in another embodiment of the present application, the ventilation and filtering system is arranged between the upper airtight glove box 1 and the lower airtight glove box 9, and shares the airflow passage with the air suction device 12. The density of formic acid vapor is greater than that of air. It volatilizes in large quantities under heating conditions and then deposits downward. The formic acid vapor is absorbed in time by the air suction device arranged around the heating stirrer 2 to prevent explosion.
[0044] like Figure 1-Figure 4 As shown, in another embodiment of the present application, the solid-liquid separator 8 includes an inner cylinder 805, a funnel 801 arranged in the upper airtight glove box 1 and an outer cylinder 802 arranged in the lower airtight glove box 9, the bottom of the outer cylinder 802 is locked by a plug 803 through a Morse taper seal, and a filter membrane 806 is fixed to the bottom of the inner cylinder 805 through a sealing ring 807, and the pore size of the filter membrane 806 is 30-50 microns.
[0045] The solid-liquid separator 8 includes a funnel 801, an outer cylinder 802, a plug 803, a sealing cone 804, an inner cylinder 805, a filter membrane 806, a sealing ring 807, and a liquid level 808. The lower end of the funnel 801 is sealed with the upper end of the outer cylinder 802, and the outer cylinder 802 passes through the bottom surface of the upper airtight glove box 1. The lower hole of the outer cylinder 802 and the plug 803 can be sealed with a sealing cone 804. The sealing cone 804 is preferably a Morse taper that can be sealed and self-locking. The lower end of the inner cylinder 805 is blocked by the filter membrane 806, and the connection between the lower end of the inner cylinder 805 and the filter membrane 806 is preferably a sealing ring 807. The pore size of the filter membrane 806 is preferably 30 to 50 micron sieve holes.
[0046] The present application also provides a method for preparing a copper conductive ink material, which is manufactured using any of the aforementioned copper conductive ink material preparation devices.
[0047] like Figure 1-Figure 4 As shown, in another embodiment of the present application, the following steps are included:
[0048] S1: Place the quartz sealed bottle 3 encapsulating the copper sulfate solution, the quartz sealed bottle 3 encapsulating the formic acid, the empty quartz sealed bottle 3 and the vacuum-packed sodium carbonate powder into the upper airtight glove box 1, place the empty quartz sealed bottle 3 into the lower airtight glove box 9, complete the sealing of the upper airtight glove box 1 and the lower airtight glove box 9, and start the ventilation and filtration system;
[0049] Place the quartz sealed bottle 3 encapsulated with copper sulfate solution, the vacuum-packed sodium carbonate powder bag 7, the quartz sealed bottle 3 encapsulated with formic acid, and the empty quartz sealed bottle 3 into the upper airtight glove box 1 and close the upper airtight door 103; place the empty quartz sealed bottle into the lower airtight glove box 9, and close the lower airtight door 903; turn on the ventilation and filtration system to reduce the number of dust particles in the upper airtight glove box.
[0050] S2: heating and stirring the copper sulfate solution, and adding the solution to the sodium carbonate powder injector and the formic acid liquid injector 5;
[0051] The operator opens the bottle cap of the quartz sealed bottle 3 containing the copper sulfate solution through the upper rubber gloves 902 outside the upper airtight glove box 1, places it on the heating stirrer 2, and puts the magnetic stirring bar equipped with the heating stirrer 2 into the quartz sealed bottle 3; the operator opens the vacuum-packed sodium carbonate powder bag 7 through the upper rubber gloves 902 outside the upper airtight glove box 1, and adds sodium carbonate powder to the powder injector 4; the operator opens the bottle cap of the formic acid inside the quartz sealed bottle 3 through the upper rubber gloves 902 outside the upper airtight glove box 1, and adds formic acid liquid to the formic acid injector 5. The copper sulfate solution inside the quartz sealed bottle 3 is continuously stirred by the m×n heating stirrers 2.
[0052] S3: adding sodium carbonate to the copper sulfate solution through a sodium carbonate powder injector under heating and stirring conditions until the sodium carbonate is completely dissolved, and controlling the air pressure in the upper airtight glove box to 98-104 kPa through an air suction device to obtain a sodium carbonate-copper sulfate mixed solution;
[0053] The sodium carbonate powder injector 4 sequentially adds sodium carbonate powder into the m×n quartz sealed bottles 3 containing the copper sulfate solution according to the high throughput design amount; the heating stirrer 2 stirs the copper sulfate solution and the sodium carbonate powder until the sodium carbonate powder is completely dissolved and copper carbonate is generated, and the chemical formula thereof is as follows;
[0054] 2GuSO4+2Na2CO3+H2O→Cu2(OH)2CO3+2Na2SO4+CO2;
[0055] Carbon dioxide gas is generated, and the gas pressure is stably controlled by the air suction device of the upper airtight glove box 1.
[0056] S4: Separating the sodium carbonate-copper sulfate mixed solution by a solid-liquid separator 8 to obtain copper carbonate hydroxide crystals, purifying and recovering the copper carbonate hydroxide crystals;
[0057] The liquid prepared in step S3 is placed in the funnel 801 of the solid-liquid separator 8 to separate the copper carbonate hydroxide crystals and the sodium sulfate solution, and the precipitated copper carbonate hydroxide crystals are harmlessly recovered.
[0058] S5: adding formic acid to the copper carbonate hydroxide crystals through the formic acid injector 5, heating and stirring, and controlling the air pressure in the upper airtight glove box 1 to 98-104 kPa through the suction device 12 to obtain a copper carbonate hydroxide-formic acid mixed solution;
[0059] Use a formic acid injector 5 to sequentially add formic acid into m×n quartz sealed bottles 3 containing copper carbonate hydroxide crystals according to the amount designed for high throughput. Heat and stir during the reaction process. During the reaction process, the liquid changes from cyan to blue. The chemical formula is as follows:
[0060] Cu2(OH)2CO3+4HCO2H→2(HCO2)2Cu+CO2+3H2O;
[0061] This process generates carbon dioxide gas, and the gas pressure is stably controlled by the suction device of the upper airtight glove box 1 .
[0062] S6: distilling the sodium carbonate hydroxide-formic acid mixed solution obtained in step S5 to obtain a copper formate solution;
[0063] S7: Separating the copper formate solution by a solid-liquid separator 8 to obtain copper formate crystals, purifying and recovering the copper formate crystals;
[0064] All quartz sealed bottles 3 are covered with sealing caps, and the gas and dust inside the upper airtight glove box 1 and the lower airtight glove box 9 are rendered harmless through a ventilation and filtration system.
[0065] S8: The air inside the upper airtight glove box 1 is replaced with argon through the ventilation and filtration system, and the copper formate crystals are taken and heated to 200°C to prepare copper nanoparticle size test samples. The particle size of copper nanoparticles directly affects the conductive properties of the conductive ink. Smaller particle size helps to form a more continuous conductive network, thereby reducing resistivity and improving conductivity. During the sintering process, copper nanoparticles with smaller particle size are more likely to form a dense conductive film, reduce porosity and impurity content, and thus obtain better conductive properties. Therefore, after the preparation of copper formate is completed, the air inside the upper airtight glove box 1 is first replaced with argon through the ventilation and filtration system, and then the heating function of the heating stirrer 2 is used to heat the copper formate crystals to prevent the oxygen in the air from oxidizing the produced copper, and at the same time prevent the explosion of oxygen and the produced hydrogen. The chemical formula for preparing copper by heating the copper formate crystals is:
[0066] (HCO2)2Cu→Cu+2CO2+H2;
[0067] The technology of preparing copper conductive ink by copper formate crystallization is an existing public technology and can be prepared using the technical solution provided in the technical document "A particle-free copper conductive ink and conductive copper film for 3D inkjet printing and a preparation method thereof".
[0068] like Figure 1-Figure 4 As shown, in another embodiment of the present application,
[0069] Step S4, separating the copper carbonate-sodium sulfate mixed solution by a solid-liquid separator to obtain copper carbonate hydroxide crystals, comprises: placing the sodium carbonate-copper sulfate mixed solution obtained in step S3 into the funnel 801 of the solid-liquid separator 8; placing the inner cylinder 805 into the funnel 801 from top to bottom, and due to the gravity of the inner cylinder 805, the sodium sulfate solution passes through the sieve holes of the filter membrane 806 and enters the inner cylinder 805, and the copper carbonate hydroxide crystals are intercepted by the filter membrane 806 in the area between the inner cylinder 805 and the funnel 801.
[0070] Step S7 of separating the copper formate solution by the solid-liquid separator 8 to obtain copper formate crystals comprises: placing the copper formate solution obtained in step S6, which is a mixture of copper formate crystals and water, into the funnel 801 of the solid-liquid separator 8; placing the inner cylinder 805 into the funnel 801 from top to bottom, and due to the gravity of the inner cylinder 805, the prepared solution will pass through the sieve holes of the filter membrane 806 into the inner cylinder 805 to form a solution containing impurities, and the copper formate crystals will be intercepted by the filter membrane 806 in the area between the inner cylinder 805 and the funnel 801.
[0071] The liquid level 808 is controlled not to exceed the bottom of the upper airtight glove box during the solid-liquid separation process. The outer cylinder 802 can accommodate liquid at a height of 20-40 cm below the bottom of the upper airtight glove box to control the pressure above the plug 803. The plug 803 and the outer cylinder 802 are made of polytetrafluoroethylene.
[0072] like Figure 1-Figure 4 As shown, in another embodiment of the present application,
[0073] Step S4 purifies and recovers the copper carbonate hydroxide crystals, including: adding distilled water between the funnel 801 and the inner cylinder 805, extracting the liquid inside the inner cylinder 805 until the copper carbonate hydroxide crystals are purified, collecting the precipitated copper carbonate hydroxide crystals, and cleaning the inner cylinder 805 and the sealing cone 804;
[0074] Purification of copper carbonate hydroxide crystals: distilled water is added between the funnel 801 and the inner cylinder 805 through the distilled water access tube, and sodium sulfate solution is extracted from the inner cylinder 805. The process is repeated until a predetermined number of times, or the concentration of the sodium sulfate solution extracted from the inner cylinder 805 reaches a predetermined value after detection, and then the purification of copper carbonate hydroxide crystals is completed, and the precipitated copper carbonate hydroxide crystals are collected and stored in a quartz sealed bottle 3;
[0075] Take out the inner cylinder 805 and clean it, pull out the plug 803, clean the sealing cone 804, reinsert the plug 803 for the next experiment, and transfer the quartz sealed bottle 3 containing copper carbonate hydroxide crystals in the lower airtight glove box 9 to the heating stirrer 2 in the upper airtight glove box 1.
[0076] Step S7 of purifying and recovering the copper formate crystals includes: filling ethanol solution between the funnel 801 and the inner cylinder 805, extracting the liquid inside the inner cylinder 805 until the purification of the copper formate crystals is completed, collecting the precipitated copper formate crystals, and cleaning the inner cylinder 805 and the sealing cone surface 804.
[0077] Crystallization and purification of copper formate: add ethanol solution between the funnel 801 and the inner cylinder 805 through the ethanol access tube, extract ethanol solution from the inner cylinder 805, repeat this process until a predetermined number of times, or until the impurity concentration of the solution extracted from the inner cylinder 805 reaches a predetermined value after detection, then the crystallization and purification of copper formate is completed, and stored in the quartz sealed bottle 3 and covered with a sealing cap.
[0078] Take out the inner cylinder 805 and clean it, pull out the plug 803, clean the sealing cone 804, and insert the plug 803 back for the next experiment.
[0079] In another embodiment of the present application, during the distillation process of step S6, the liquid is kept from boiling, and it is required that copper formate cannot be completely crystallized when the distillation ends. Copper formate is easily decomposed at high temperatures, and the liquid boils, and the temperature will rise to a higher level, which will cause the decomposition of copper formate, thereby affecting the purity and yield of the product. By controlling the temperature, the liquid is not boiled, and this thermal decomposition phenomenon can be effectively avoided. At the same time, incomplete crystallization helps to control the shape and size of copper formate crystals. Too fast a crystallization rate may cause an incomplete crystal structure and uneven particle size, which affects the application of copper formate crystallization to prepare copper conductive ink. The complete crystallization of the liquid will cause the impurities in the solution to crystallize together, reducing the purity of copper formate, and the distillation process keeps incomplete crystallization to reduce the entrainment of impurities.
[0080] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should be included in the protection scope of the present application.
Claims
1. A copper conductive ink material preparation device, characterized in that: It comprises an upper airtight glove box and a lower airtight glove box stacked up and down, a solid-liquid separator is arranged between the upper and lower airtight glove boxes; a heating stirrer is arranged in the upper airtight glove box, and an air suction device is arranged around the heating stirrer; a sodium carbonate powder injector, a formic acid liquid injector, a copper sulfate solution sealed bottle and a copper formate crystal sealed bottle are arranged in the upper airtight glove box, a ventilation and filtration system is arranged in the upper airtight glove box, and the ventilation and filtration system is provided with an argon gas supply port, a drying box is arranged in the lower airtight glove box, both the upper and lower airtight glove boxes are provided with operating holes, operating gloves and airtight doors, and an air pressure detection device, a distilled water inlet pipe and an ethanol inlet pipe are arranged in the upper airtight glove box.
2. The copper conductive ink material preparation device according to claim 1, characterized in that: The top of the airtight door is provided with an air curtain device for supplying air from top to bottom.
3. The copper conductive ink material preparation device according to claim 1, characterized in that: The heating stirrers are provided in m×n numbers, wherein m is the number of rows, n is the number of columns, m≥2, n≥2.
4. The copper conductive ink material preparation device according to claim 2, characterized in that: The ventilation and filtering system is arranged between the upper airtight glove box and the lower airtight glove box, and shares an air flow passage with the air intake device.
5. The copper conductive ink material preparation device according to claim 3, characterized in that: The solid-liquid separator comprises an inner cylinder, a funnel arranged in an upper airtight glove box and an outer cylinder arranged in a lower airtight glove box. The bottom of the outer cylinder is locked by a plug through a Morse taper seal. A filter membrane is fixed to the bottom of the inner cylinder through a sealing ring. The pore size of the filter membrane is 30-50 microns.
6. A method for preparing a copper conductive ink material, characterized in that: The copper conductive ink material is manufactured using the copper conductive ink material preparation device as described in any one of claims 1 to 5.
7. The method for preparing a copper conductive ink material according to claim 6, characterized in that: The following steps are involved: S1: Place a quartz sealed bottle containing copper sulfate solution, a quartz sealed bottle containing formic acid, an empty quartz sealed bottle, and vacuum-packed sodium carbonate powder into an upper airtight glove box, place the empty quartz sealed bottle into a lower airtight glove box, complete the sealing of the upper and lower airtight glove boxes, and start the ventilation and filtration system; S2: heating and stirring the copper sulfate solution, and adding the material to the sodium carbonate powder injector and the formic acid liquid injector; S3: adding sodium carbonate to the copper sulfate solution through a sodium carbonate powder injector under heating and stirring conditions, heating and stirring until the sodium carbonate is completely dissolved, and controlling the air pressure in the upper airtight glove box to 98-104 kPa through an air suction device to obtain a sodium carbonate-copper sulfate mixed solution; S4: separating the sodium carbonate-copper sulfate mixed solution by a solid-liquid separator to obtain copper carbonate hydroxide crystals, purifying and recovering the copper carbonate hydroxide crystals; S5: adding formic acid to the copper carbonate hydroxide crystals through a formic acid injector, heating and stirring, and controlling the air pressure in the upper airtight glove box to 98-104 kPa through an air suction device to obtain a copper carbonate hydroxide-formic acid mixed solution; S6: distilling the sodium carbonate hydroxide-formic acid mixed solution obtained in step S5 to obtain a copper formate solution; S7: separating the copper formate solution by a solid-liquid separator to obtain copper formate crystals, purifying and recovering the copper formate crystals; S8: The air inside the upper airtight glove box is replaced with argon gas through a ventilation and filtration system, and copper formate crystals are taken and heated to 200° C. to prepare a copper nanoparticle size detection sample.
8. The method for preparing the copper conductive ink material according to claim 7, characterized in that: The step S4 of separating the copper carbonate-sodium sulfate mixed solution by a solid-liquid separator to obtain copper carbonate hydroxide crystals comprises: placing the sodium carbonate-copper sulfate mixed solution into a funnel of the solid-liquid separator, placing the inner cylinder into the funnel from top to bottom, allowing the sodium sulfate solution to pass through the sieve holes of the filter membrane into the inner cylinder, and the copper carbonate hydroxide crystals are intercepted by the filter membrane in the area between the inner cylinder and the funnel; The step S7 of separating the copper formate solution by a solid-liquid separator to obtain copper formate crystals comprises: placing the copper formate solution into a funnel of the solid-liquid separator; placing the inner cylinder into the funnel from top to bottom, the copper formate solution enters the inner cylinder through the sieve holes of the filter membrane to form a solution containing impurities, and the copper formate crystals are intercepted by the filter membrane in the area between the inner cylinder and the funnel.
9. The method for preparing a copper conductive ink material according to claim 7, characterized in that: The purification and recovery of the copper carbonate hydroxide crystals in step S4 includes: adding distilled water between the funnel and the inner cylinder, extracting the liquid inside the inner cylinder until the purification of the copper carbonate hydroxide crystals is completed, collecting the precipitated copper carbonate hydroxide crystals, and cleaning the inner cylinder and the sealing cone surface; The purification and recovery of copper formate crystals in step S7 includes: filling ethanol solution between the funnel and the inner cylinder, extracting the liquid inside the inner cylinder until the purification of the copper formate crystals is completed, collecting the precipitated copper formate crystals, and cleaning the inner cylinder and the sealing cone surface.
10. The method for preparing a copper conductive ink material according to claim 7, characterized in that: During the distillation process in step S6, the liquid is kept from boiling, and the copper formate is required not to be completely crystallized at the end of the distillation.
Citation Information
Patent Citations
Preparation method of composite conductive ink containing copper particles and organic copper salt
CN112111197A
A particle-free copper conductive ink and conductive copper film for 3D inkjet printing and a preparation method thereof
CN116285503B